Sardegna 2050 CO2 zero: sei progetti strategici - Tramontin, Antonio; Zola, Francesca (UNICApress, 2020)
After the Covid-19 pandemic, environmental rebalancing became the vital limit for humans in the third millennium. The inevitable global scenario, where perhaps accidents have crossed, can be looked at from another horizon, as a mosaic of local operations on the environment. The design research by the Faculty of Engineering and Architecture of the University of Cagliari, in concert with the University of Applied Arts in Vienna, and funded by the Autonomous Region of Sardinia, configures, with inland areas at its core, a fundamental perspective of the Regional Policies for a carbon-neutral Sardinia in the next 30 years.